TEACHING READING IN NARRATIVE TEXT BY USING STORY FRAME STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMP MUHAMMADIYAH 4 PALEMBANG - Dika Resa Septiani (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2016)
The objective of the study was to find out whether or not there was a significant difference in reading comprehension achievement between the eighth grade students of SMP Muhammadiyah 4 Palembang who are taught by using Story Frame and those who are not and to find out whether or not there was a significant difference in reading comprehension achievement between the eighth grade students of SMP Muhammadiyah 4 Palembang who are taught by using Story Frame and those who are not before and after the treatment. One of the quasi-experimental designs, nonequivalent pretest-posttest design was used. The population of the study was all of the eighth grade students of SMP Muhammadiyah 4 Palembang. Purposive sampling was used, where 30 students belonged to experimental group and 30 students belonged to control group. In collecting the data, test was used. The test was given twice to experimental and control groups, as a pretest and posttest. To verify the hypotheses, the data of pretest and posttest of the experimental and control groups were analyzed by using independent sample t-test and paired sample t-test in SPSS program. The finding showed that the p-output (sig.(2-tailed)) was 0.000 lower than 0.05 and the t-value 3.734 was higher than t-table 1.672. And than p-output from paired sample t-test was 0.000 lower than 0.05 with df=29 (1.699) and the t-value 8.362. Therefore, null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that teaching narrative reading comprehensionby using Story Frame had a significant effect on the students’ reading comprehension achievement.